2020
DOI: 10.1210/clinem/dgaa825
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Hospitalization in Adults with Type 1 Diabetes: Results from the T1D Exchange Multicenter Surveillance Study

Abstract: Context Diabetes mellitus is associated with increased COVID-19 morbidity and mortality, but there is little data focusing on outcomes in people with type 1 diabetes. Objective The objective of this study was to analyze characteristics of adults with type 1 diabetes for associations with COVID-19 hospitalization. Design An observational multi-site cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 11 publications
1
49
2
2
Order By: Relevance
“…Fifteen studies were finally included: Eight studies are retrospective cohort studies, three are cross-sectional studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] ], two are retrospective case-control studies [ 25 , 26 ], one is retrospective case-series [ 27 ], and one was a commentary with no clear report of a study design, but the study included original data [ 28 ]. The studied populations were patients with COVID-19 alone in two studies [ 22 , 27 ], patients with T1DM alone in five studies [ 14 , 21 , 23 , 24 , 28 ], patients with both COVID-19 and T1DM in five studies [ [18] , [19] , [20] , 29 , 30 ], and patients with either COVID-19 and T1DM (case group) and patients with T1DM alone or with COVID-19-like disease (control group) in two studies [ 25 , 26 ]. The sample size of included studies ranged from 32 participants [ 18 ] to 264,390 participants [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen studies were finally included: Eight studies are retrospective cohort studies, three are cross-sectional studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] ], two are retrospective case-control studies [ 25 , 26 ], one is retrospective case-series [ 27 ], and one was a commentary with no clear report of a study design, but the study included original data [ 28 ]. The studied populations were patients with COVID-19 alone in two studies [ 22 , 27 ], patients with T1DM alone in five studies [ 14 , 21 , 23 , 24 , 28 ], patients with both COVID-19 and T1DM in five studies [ [18] , [19] , [20] , 29 , 30 ], and patients with either COVID-19 and T1DM (case group) and patients with T1DM alone or with COVID-19-like disease (control group) in two studies [ 25 , 26 ]. The sample size of included studies ranged from 32 participants [ 18 ] to 264,390 participants [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported the clinical findings of COVID-19 in patients with T1DM [ 18 , 25 , 27 , 30 ]. Nausea and vomiting were the most common presentation of COVID-19, accounting for 71.40% (5/7) of patients in the study of Al Hayek et al [ 18 ] Dry cough was the most common presentation (51%; 58/113) in the study of O'Malley et al [ 30 ] Fever was the most common presentation (89.9%; 62/69) in the study of Yang et al [ 27 ] Finally, elevated blood glucose level was the most common presentation both in the case group (COVID-19 and T1DM; 48.5%) and in the control group (COVID-19-like disease and T1DM; 51.60%) in the study of Ebekozien et al [ 25 ] The radiographic findings of patients with both COVID-19 and T1DM were not reported in any of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations